ANALYSIS OF THE FINANCIAL PERFORMANCE OF THE DRINKING WATER PUBLIC COMPANY (PERUMDAM) - ASRINI; Kasim, Muhammad Yunus; Z, Fatlina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
This study aims to assess the profitability, liquidity, solvency, and financial performance ratios of the public drinking water company (PERUMDAM) in Uwe Lino, Donggala Regency, in accordance with the Decree of the Chairman of BPP-SPAM Number 022 / KPTS / K-6 / IV / 2010. This is quantitative research with descriptive analysis. Using a modified performance appraisal analysis based on a statistical range across three assessment categories: healthy, less healthy, and sick. Overall, the development of the company's financial ratios indicates a very positive trend from 2019 to 2023. Profitability (ROE), Liquidity (Cash Ratio), and solvency show consistent improvement, indicating that the company is in an improving financial condition. The primary concern is the effectiveness of the billing-to-operating ratio. The Financial Performance of the Drinking Water Regional Public Company (PERUMDAM) in Uwe Lino, Donggala Regency, is in the less healthy category overall but shows progress from 2019 to 2023